Effect of egg flour as an alternative protein source on biochemicial parameters of rainbow trout - Kelestemur, Tuna G.; Cambay, Z.; Kelestemur, N.; Uslu, A. A. (Iranian Fisheries Science Research Inst-Ifsri, 2021)
In this study, the effects of diets supplemented with 13.5%, 22.5%, 31.5% and 51.7% (diet groups; D-1, D-2, D-3, D-4, respectively) egg flour instead of fish meal on blood proteins, lipids and ion levels pigmentation of rainbow trout were investigated. Fish (initial weight and length, 72.87 +/- 0.73 g, 18.11 +/- 0.06 cm, respectively) were distributed into 15 fiberglass rectangular (200 cmx40 cm x40 cm) tanks in a 5x3 experimental design (5 diet groupsx3 replicate groups) with a density of 30 juvenile rainbow trout (Oncorhynchus mykiss) per tank. Fish were fed with four different diets containing egg flour, and a basal diet (not supplemented) for 12 weeks. The results of oneway ANOVA test showed that blood proteins, lipids and ion levels of fish were affected by dietary supplementation of egg flour. Serum glucose level in the D-4 group was significantly lower (p<0.05) than the other diet groups. Serum total protein (TP) levels in D-4 and D-3 group were significantly higher (p<0.05) than the other diet groups. Serum uric acid, creatinin, blood urea nitrogen (BUN), and urea levels increased in the D-4 group. It was concluded that replacing with 50% egg flour in rainbow trout diet decreased the serum ion levels of magnesium (Mg+), calcium (Ca+), sodium (Na+), potassium (K+) and phosphorus (P) %. However, serum Cl- levels were not statistically different among the groups (p>0.05). On the other hand, serum lipid levels concluded an increasing tendency with the increasing percentage of supplement in the fish diet. The results of the present work indicate that compared to the experimental diets, it can also be concluded that when egg flour is used in rations of over 50% in rainbow trout it has significantly negative effects on blood protein, lipid and ion concentration.
Keywords: Rainbow trout; Animal protein; Egg flour; Serum protein; Serum lipid; Serum ion